Clinical manifestations of pandemic (H1N1) 2009 in the ambulatory setting - Vítor Duque; João Vaz; Vanda Mota; Célia Morais; Saraiva da Cunha; António Meliço-Silvestre (Journal of Infection in Developing Countries)
Introduction: In June 2009, the World Health Organization declared an influenza pandemic associated with the pandemic (H1N1) 2009 strain. It was summer in the northern hemisphere, and therefore travelling and vacation time, which also provided an increased opportunity for the dissemination of respiratory diseases.